Perceptions of final-year students and subject librarians on the adequacy of library user education programmes at the University of Limpopo - Shai, Kgaogelo Samson (My University, 2020)
The purpose of the study was to investigate the perceptions of final-year students and subject librarians towards the adequacy of the structure and content of library user education programmes at the University of Limpopo (UL) library. Both quantitative and qualitative research methodologies were followed and a descriptive and phenomenological research designs respectively were also adopted for the study. The population for the study consisted of 260 final year students and eight (8) subject librarians, who were selected through systematic random sampling (students) and purposive sampling methods (subject librarians). Data were collected from students and subject librarians using questionnaires and semi-structured interviews. An analysis of content for UL library website was also conducted to triangulate the results of the study. Quantitative and qualitative were analysed using excel spreadsheet and thematic analysis respectively. The final year students at the UL showed some positive perceptions and attitudes towards the library in general and to the adequacy of the content and structure of its user education programmes. They are of the opinion that library staff should commit to good customer care principles and regular delivery of user education programmes, and that user education programmes at the UL library should be a credit-bearing module/course for all first-level students in all four faculties. On the structure and content, the findings of the study revealed that the UL library provides user education programmes such as library orientation, bibliographic instruction, information literacy, on-on-one training, online interactive course, library guides and brochures with different content and for different library users. Website content analysis found subject LibGuides were used as platforms for advertising Bibliographic Instruction programmes. However, impediments experienced by subject librarians towards a comprehensive delivering of user education programmes at the UL library include insufficient time allocated to user education programmes, lack of venues to conduct user education sessions, inaccessibility of social media tools, LibGuides not going live, insubstantial partnerships between stakeholders (academics and students) and the v library staff, and low attendance of user education programmes by undergraduate students. The research recommends that there should be a credit-bearing and compulsory information literacy programme offered as part of the curriculum at first levels of study at the UL. Furthermore, library staff need to have a continuous engagement with both academic staff and students, and notify them about important events within the library. The library website should also be upload recorded online user education sessions which can be accessed by library users any time. The library management should also engage ICT to open the social media platforms as that is where most students prefer to interact. This can also be used to deliver user education programmes.
Thesis (M.A. (Information Studies)) -- University of Limpopo, 2020
Keywords: User perception; Subject librarians; User education programmes; Academic library; University of Limpopo; Bibliographic instruction; Library orientation and information literacy; Course integrated user education; Information services -- User education; Information services -- Study and teaching -- Activity programs; Library orientation; Information literacy